Duodenal villous morphology assessed using magnification narrow band imaging correlates well with histology in patients with suspected malabsorption syndrome. Issue 6 (26th March 2014) - Dutta, Amit Kumar; Sajith, Kattiparambil Gangadharan; Shah, Gautam; Pulimood, Anna Benjamin; Simon, Ebby George; Joseph, Anjilivelil Joseph; Chacko, Ashok
<x xml:space="preserve">Abstract</x> Background and Aim Narrow band imaging with magnification enables detailed assessment of duodenal villi and may be useful in predicting the presence of villous atrophy or normal villi. We aimed to assess the morphology of duodenal villi using magnification narrow band imaging and correlate it with histology findings in patients with clinically suspected malabsorption syndrome. Methods Patients with clinical suspicion of malabsorption presenting at a tertiary care center were prospectively recruited in this diagnostic intervention study. Patients underwent upper gastrointestinal endoscopy using magnification narrow band imaging. The villous morphology in the second part of the duodenum was assessed independently by two endoscopists and the presence of normal or atrophic villi was recorded. Biopsy specimen was obtained from the same area and was examined by two pathologists together. The sensitivity and specificity of magnification narrow band imaging in detecting the presence of duodenal villous atrophy was calculated and compared to the histology. Results One hundred patients with clinically suspected malabsorption were included in this study. Sixteen patients had histologically confirmed villous atrophy. The sensitivity and specificity of narrow band imaging in predicting villous atrophy was 87.5% and 95.2%, respectively, for one endoscopist. The corresponding figures for the second endoscopist were 81.3% and 92.9%, respectively. The interobserver agreement was very good with a kappa value of 0.87. Conclusion Magnification narrow band imaging performed very well in predicting duodenal villous morphology. This may help in carrying out targeted biopsies and avoiding unnecessary biopsies in patients with suspected malabsorption.